Analisis Mutu Pelayanan Terhadap Tingkat Kepuasan Dan Minat Berkunjung Kembali Pasien Di Puskesmas Pasar Rebo Tahun 2015 - Elwindra Elwindra; Petronela Ruslini (STIKes Persada Husada Indonesia, 2015)
Puskesmas Pasar Rebo vision is to promote the realization of quality health services leading to an independent healthy society. The issues highlighted by the public in the scope of public services quality indicated there is still found weaknesses and deviation that could be influential towards public’s satisfaction. This research is important to be carried out as a follow-up research a year earlier towards Community Satisfaction Index in Puskesmas Pasar Rebo to find out if the improved service quality rendered by the Puskesmas Pasar Rebo to the public inter-relates to satisfaction and patients’ interest for revisits. This is a quantitative research with a cross-sectional approach of 100 sample respondents. This research applied an analytical survey using Importance-Performance Analysis with Cartesian Diagram. The results showed that the service quality categorised as good with level of conformity (comparison between expectation and reality) at 80,1%. Elements which are considered best meets the expectations of respondents were the friendliness and attention of the doctor during treatment 92.4%, while the element which least met the expectations of patients was the sufficient and comfortable waiting area of 76.3%. This research found a significant association between education and patient satisfaction, while for age, gender, occupation, distance and visitation interests showed no significant relationship with patient satisfaction. Importance Performance Analysis result shows the dimensions of service quality of Responsiveness (Quick response) are in quadrant A, which means the health center should expediate and be more responsive to meet customer expectations.